LAYANAN BIMBINGAN KELOMPOK BERBASIS ONLINE UNTUK MENCEGAH PERILAKU MENYONTEK SISWA MA - Aditya Achmad Qoyum; Euis Eti Rohaeti; Maya Masyita Suherman (IKIP Siliwangi, 2022)
This research was motivated by reports from subject teachers related to cheating behavior. Through online group guidance with discussion techniques, it is expected to be able to prevent students' cheating behavior in class XI IPS MA Al-Mukhtariyah Mande. The purpose of this study was to determine the implementation of online group guidance services for students to prevent cheating behavior, to determine student responses to online group guidance services to prevent cheating behavior, to find out the obstacles or difficulties experienced by class students when participating in online group guidance services aimed at preventing cheating behavior, knowing the obstacles or difficulties faced by guidance and counseling teachers during the preparation and implementation of online group guidance services for students to prevent cheating behavior. The research method used is descriptive with a qualitative approach. Data collection techniques used are interviews, observation and documentation. The results showed that online group guidance services with discussion techniques helped students in preventing cheating behavior. The responses of the five students stated that they were happy to know information about the impact of cheating. At the time of the implementation of the service students were constrained by an unstable signal. Keywords: Online Group Guidance, Discussion Techniques, Cheating Behavior